ISLAM WASAá¹¬ÃYAH DALAM PERSPEKTIF HADIS: Dari Konsep Menuju Aplikasi - Ardiansyah, Ardiansyah (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2016)
This article tries to explain the concept of Islamic wasaá¹Ã®yah (Islamic moderate) from the prophetic á¸¥adÃ®th point of view. It, then, attempts to elaborate the prophetâs attitudes and sayings which have to do with the issue of moderation. It should be noted that many researches have focused more on the polemical á¸¥adÃ®th that are mistreated by some radical Muslims to legitimate their arguments, but are little to investigate the moderation side of the á¸¥adÃ®th. Methodologically, the article employs thematic method to collect á¸¥adÃ®th from the classical book and then analyze it by the contextual frame. By searching of the terminological explanation of moderation, it can be summarized that the prophetic á¸¥adÃ®th has little to say about moderation in term of wasaá¹Ã®yah, but there has ample of word which is equivalent to the term, that is al-qaá¹£d. Those á¸¥adÃ®th has brought several principles and characteristics, such like al-khayrÃ®yah (chosen), al-âadÃ¢lah (fairness), al-tasÃ¢muá¸¥ (tolerant attitude), al-tawÃ¢zun (balance), al-istiqÃ¢mah (consistency), and rafâ al-á¸¥araj (eliminating difficulties). Those principles are significant in terms of demonstrating the peaceful life and arguing the violent and intolerant conducts. The contextual analysis of the á¸¥adÃ®th has argued that those values should be put on the universal principles which Islam has come along with.